2019
DOI: 10.1515/labmed-2018-0323
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 in the pathogenesis of pulmonary artery hypertension

Abstract: Background Interleukin (IL)-13 is a regulatory factor of tissue remodeling and is involved in the pathogenesis of pulmonary artery hypertension (PAH). However, the implications of IL-13 in PAH remains uncertain. This article aims to describe the current knowledge on production and function of IL-13 and its receptors in the mechanisms of PAH. Content The study materials of this article were based on comprehensive literature retrieval of publications of IL-13 in PAH. These study materials were carefully reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…IL-13 activates the intracellular downstream signaling molecules by binding with IL-13Rα1/IL-4Rα heterodimer. 30 We also observed an increased IL-13Rα1 expression in the SMGs of IgG4-RS patients (Fig. 1d, e, f ).…”
Section: Discussionsupporting
confidence: 63%
“…IL-13 activates the intracellular downstream signaling molecules by binding with IL-13Rα1/IL-4Rα heterodimer. 30 We also observed an increased IL-13Rα1 expression in the SMGs of IgG4-RS patients (Fig. 1d, e, f ).…”
Section: Discussionsupporting
confidence: 63%
“… 36 On the other hand, IL-13 is an important regulatory factor involved in the pathogenesis of pulmonary vascular remodeling and in the development of pulmonary artery hypertension. 37 Concerning the role of IL-13 in inflammatory heart diseases, it was demonstrated that IL-13 deficient mice develop severe myocarditis, having poor prognosis, and that experimental administration of IL-13 could significantly improve heart inflammation and cardiac injury induced by myocarditis. 38 , 39 IL-13 is also associated with progression of valvular heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, we have also shown that 11 genes were a direct target of miR-let-7i-5p, which upregulation modulates the proliferation of human PASMCs. Among them, Interleukin13 (IL13) upregulation induces PASMCs in the pulmonary artery through signal transducer and activator of transcription STAT6 or through phosphatidylinositol 3-kinase (PI3K), STAT3 and mitogen activated protein kinase (MAPK) pathways (Yuan, 2019). Oxidant, arginase 2 (ARG2) and hypoxia-inducible factor 1α (HIF1) are also involved in the proliferation of PASMCs (Yuan, 2019).…”
Section: Outcome Evolution In Pulmonary Thromboembolism (Apte and Cteph)mentioning
confidence: 99%
“…Among them, Interleukin13 (IL13) upregulation induces PASMCs in the pulmonary artery through signal transducer and activator of transcription STAT6 or through phosphatidylinositol 3-kinase (PI3K), STAT3 and mitogen activated protein kinase (MAPK) pathways (Yuan, 2019). Oxidant, arginase 2 (ARG2) and hypoxia-inducible factor 1α (HIF1) are also involved in the proliferation of PASMCs (Yuan, 2019). The experimental Schistosomiasisassociated PAH potentially depends on upregulation of IL-13, which can activate TGF-β1 via phospho-STAT6 signaling, or via increased matrix metalloproteinase-inducing muscular hypertrophy and periadventitial fibrosis in pulmonary arteries (Graham et al, 2010).…”
Section: Outcome Evolution In Pulmonary Thromboembolism (Apte and Cteph)mentioning
confidence: 99%
See 1 more Smart Citation